Influence of Hydrophilic-Lipophilic Balance (HLB) parameter of F98 and F127 polymers on the effectiveness of the formation of gold nanoparticles and encapsulation of the drug capecitabine for the treatment of stomach cancer (Research, Society and Development, 2022)
Pluronic F98 and F127 have a higher hydrophilic percentage (70 wt%), in the case of Pluronic F127 and 80% in the case of F98. The article consists of a comparison of the LBL parameter and its influence on the formation of Gold Nanoparticles. These nanoparticles are chosen because they have low toxicity, as well as being effective in medicinal application. Stomach cancer has a high incidence. There is the formation of compounds with a hydrophobic core of polypropylene oxide (PPO) and a hydrophilic crown of polyethylene oxide (PEO). The Pluronic-Nanoparticle system will be gradually released in the patient's body, for less toxicity and greater treatment efficacy. The methodologies used in this first phase are the bibliographic sources and their survey and the use of the main databases for this purpose.